The epistemological revolution of indigenous women: a glimpse through the proposals of four contemporary women thinkers - Arce-Rodríguez, Dora (2021)
This article examines the contributions of four indigenous Guatemalan  women: Lorena Cabnal, Aura Cumes, Gladys Tzul and Emma Chirix. The focus of the study is centered on three lines of reflection common to these authors, namely, the recovery of the indigenous cosmovision, the critique  of hegemonic feminisms, and the vindication of the body, context and subjectivity as places of enunciation. From the dialogue between their proposals, it is evident the development of a particular epistemic corpus that focuses on subjectivity and the socio-cultural and historical context of  women as starting points to understand reality.